2018
DOI: 10.1123/jsr.2017-0043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kinesiology Taping on Scapular Reposition Accuracy, Kinematics, and Muscle Activity in Athletes With Shoulder Impingement Syndrome: A Randomized Controlled Study

Abstract: Our study identified the positive effects of KT on scapular joint position sense and movement control. Future studies with a longer period of follow-up and clinical measurement might help to clarify the clinical effect and mechanisms of elastic taping in individuals with SIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 27 publications
0
48
0
2
Order By: Relevance
“…30 Lower trapezius taping showed a significant increase in scapular posterior tilt in baseball players with shoulder impingement syndrome. 31…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Lower trapezius taping showed a significant increase in scapular posterior tilt in baseball players with shoulder impingement syndrome. 31…”
Section: Discussionmentioning
confidence: 99%
“…30 Lower trapezius taping showed a significant increase in scapular posterior tilt in baseball players with shoulder impingement syndrome. 31 Moreover, the relation between the shoulder proprioception and kinematic has been previously described. [31][32][33] Shih et al 31 concluded that taping-associated immediate improvement in scapular reposition sense was accompanied by enhanced scapular kinematics including increased scapular posterior tilt and scapular upward rotation during arm elevation in the scapular plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of scapular mechanics, there have been numerous studies showing that rigid and elastic taping methods can improve scapular kinematics in the sagittal and scapular planes [7][8][9][10]. In patients with subacromial impingement syndrome, kinesiotaping of the scapula seems to decrease the activity in the upper trapezius during shoulder abduction leading to reduced functional impingement with overhead activities [10].…”
Section: Kinesiotapingmentioning
confidence: 99%
“…Specifically in baseball players with subacromial impingement, a randomized study between elastic taping and placebo taping showed that elastic taping resulted in positive changes in scapular motion and muscle performance [8]. Another randomized study in overhead athletes with subacromial impingement syndrome showed that elastic taping can have positive effects on scapular joint position sense and movement control [9]. While the results of these studies in overhead athletes seem to support the use of elastic taping as a treatment aid in managing shoulder impingement problems, future studies with a longer period of follow-up and clinical measurement might help to clarify the clinical effect and mechanisms of elastic taping in these patient populations.…”
Section: Kinesiotapingmentioning
confidence: 99%